Crispr/Cas9 Delivery for Glioma Treatment: A Systematic Review - Álvarez, Thiago Andrés Navarro; Álvarez, Ricardo Andrés Novoa; Parra, Jaime Antonio Navarro (Journal of Posthumanism, 2025)
CRISPR/Cas9 gene editing technology represents an interesting and promising option for treating glioblastoma patients. Different in vitro studies have demonstrated the success of the gene editing process; however, the efficacy of this technology and its delivery directly into tumor cells in vivo needs to be evaluated. A systematic review of the literature was performed to identify studies using gene editing techniques at the preclinical stage in animal models to analyze their efficacy and safety in vivo. 1463 articles were identified; five articles involved the use of CRISPR/Cas9 gene editing therapy against human cells in animal models to treat glioma. Compared with unedited controls, the gene-edited cells showed reduced tumor size, prolonged survival, no damage to off-target cells and no toxic effects. However, there is high heterogeneity among the articles identified due to the different mouse strains and different delivery methods. CRISPR/Cas9 gene editing shows promising anti-cancer effect. Further reporting of in vivo studies is expected to continue, with the potential to better control for bias and reduce heterogeneity, thereby positive effects could be corroborated.